2005
DOI: 10.1111/j.1600-0404.2005.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequent association of multiple sclerosis with varicella and zoster

Abstract: The association of these pathologies is higher than expected and suggests a possible etiological relationship of the varicella zoster virus with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…However, when reviewing retrospectively the clinical status of those positive cases we found that the blood samples in all them had been taken within the initial days of an acute relapse (13 out of 15, 87%); in contrast, all patients who were on remission at the time of blood sampling (n = 67) tested negative. While conducting this study we reviewed the medical records of all MS patients studied during the last 2 years, a total of 82 cases, in six of them (7%) we found a close association of a typical VZV infection, either varicella or zoster, closely related in time with the clinical debut of MS [15]. Although the association could be casual, this finding strengthened the epidemiological and laboratory evidences of a potential link between VZV and MS. A further study, which included the search for DNA from the most common human herpes viruses in a substantial number of MS patients who were followed from relapse until remission, corroborated our initial findings [16].…”
mentioning
confidence: 55%
“…However, when reviewing retrospectively the clinical status of those positive cases we found that the blood samples in all them had been taken within the initial days of an acute relapse (13 out of 15, 87%); in contrast, all patients who were on remission at the time of blood sampling (n = 67) tested negative. While conducting this study we reviewed the medical records of all MS patients studied during the last 2 years, a total of 82 cases, in six of them (7%) we found a close association of a typical VZV infection, either varicella or zoster, closely related in time with the clinical debut of MS [15]. Although the association could be casual, this finding strengthened the epidemiological and laboratory evidences of a potential link between VZV and MS. A further study, which included the search for DNA from the most common human herpes viruses in a substantial number of MS patients who were followed from relapse until remission, corroborated our initial findings [16].…”
mentioning
confidence: 55%
“…Histograms are from a representative MS case during relapse; the arrow shows a high fluorescent intensity of lymphocytes marked with antibodies to VZV chickenpox and zoster; interestingly, it is also effective in MS, although the mechanisms for this have not been clarified [4,10,11,16,29]. Some patients develop MS soon after varicella or zoster infection [28,29]. The VZV has a distinctive ability for multiple pathogenicity related to the age of the host and to the cells infected [36]; in this way, the same virus may cause either chickenpox or herpes zoster or, we speculate, MS.…”
Section: Discussionmentioning
confidence: 96%
“…Coincidentally, the epidemiology of MS is similar to that of varicella, high in the northern hemisphere sharply decreasing towards tropical areas [30]. Our initial study demonstrated that the antecedent of varicella in MS patients was far more frequent than that in matched controls and in the general population [25, 31]; moreover, the mean age of infection in MS patients (8 years of age) was significantly older than in controls (5 years of age). The above unexpected findings prompted us to study the possible presence of VZV in MS patients: the initial study searched for DNA from VZV in peripheral mononuclear blood cells (PBMC) from 82 MS patients [32]; results showed that only 13 (16%) were positive by polymerase chain reaction (PCR) to one or various genes specific for VZV.…”
Section: Varicella Zoster Virus and Multiple Sclerosismentioning
confidence: 98%